Nursing experience of electrolyte disturbance after resection of craniopharyngioma in a child (1例儿童颅咽管瘤切除患儿术后电解质紊乱的护理) - MA Meng (马蒙); SUN Shuang (孙爽); MA Xiaoting (马晓婷); WANG Huazhi (王华枝); Li Yuhua (李玉华) (中西医结合护理, 2022)
This paper summarized the nursing experience of a child with electrolyte disturbance after craniopharyngioma resection. Postoperative children with craniopharyngioma are prone to electrolyte disorders, and children in serious condition may have demyelination and other symptoms, directly affecting the prognosis. Medical staff should take close observation of the vital signs and consciousness, accurately record the fluid intake and output, monitor changes of body temperature, and reduce secondary damage caused by electrolyte disorders. The diet nursing should be carried out in combination with Traditional Chinese Medicine emotional nursing. (本文总结1例儿童颅咽管瘤切除术后患儿出现电解质紊乱的护理经验。颅咽管瘤切除术后患儿容易出现电解质紊乱, 严重者可出现脱髓鞘等症状, 直接影响预后效果。医护人员应严密观察患者生命体征和意识, 准确记录出入量, 监测体温变化, 减少电解质紊乱带来的继发损害; 同时给予饮食护理, 实施中医情志护理。)